Different clinical effects upon separate inhibition of coexisting EGFR and PI3KCA mutations in a lung adenocarcinoma patient. Issue 2 (February 2015) - Tiseo, Marcello; Bersanelli, Melissa; Perrone, Federica; Tamborini, Elena; Settanni, Giulio; Busico, Adele; Rossi, Giulio; Ardizzoni, Andrea; Pelosi, Giuseppe
Highlights: Mutations of PIK3CA characterize 2–4% of NSCLC. PIK3CA mutations are not-mutually-exclusive with other mutations. Shorter median survival was reported if concomitant PIK3CA and EGFR mutations. In this case, progression disease was reported with PI3K inhibitor. Benefit with EGFR-TKI is possible also with concomitant PIK3CA and EGFR mutations. Abstract: We present a very interesting case of lung adenocarcinoma carrying an uncommon EGFR exon 19 insertion with concomitant PIK3CA mutation showing dramatic and persisting improvement upon erlotinib therapy, after progression during PI3K inhibitor.